Removal of inclusions and trace elements from Al-Mg-Si alloys using refining fluxe - Kovačec, Uroš (Strojniški vestnik, 2025)
The cleanliness of aluminium alloys has a decisive effect on their properties and performance. In this work, the melts of several Al-Mg-Si alloys (6xxx series) were refined using rotary flux injection (RFI) of the salt fluxes in the industrial environment. A typical charge consisted of 25 % to 30 % external scrap, 45 % to 50 % internal scrap, and 20 % to 30 % primary aluminium. During injection, the entire melt volume was mixed uniformly. The melt was filtered using a porous ring filtration apparatus. The fraction and type of non-metallic inclusions were determined using light and scanning electron microscopy. The contents of alkali and alkaline-earth metals were determined using optical emission spectroscopy. The reduction of alkali and alkaline earth metals and the fraction of nonmetallic inclusions were used to evaluate the process efficiency and the flux selection for the regular production. An analysis of more than 100 industry charges confirmed that the flux selected after the experimental trials, consisting of a mixture of MgCl2, KCl, NaCl and CaF2, was effective in regular production.
Keywords: alkalijski element; alkall element; aluminij; aluminium; cleanlines; čistoča; flux; nekovinski vključek; non-mtalic inclusion; rafinacija taline; refinement; rotacijsko vbrizgavanje; rotary injection; talilo